THE IMPACT OF DIGITAL PAYMENT SYSTEMS ON CONSUMER BEHAVIOUR IN INDIA - Huggi, Meenakshi M; R, Bhuwaneshwari; Udagi, Kanyakumari (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The digital payments ecosystem in India has revolutionized the financial sector by shifting consumer behavior toward cashless transactions. The introduction of Unified Payments Interface (UPI), mobile wallets, debit/credit cards, and Buy Now, Pay Later (BNPL) services has significantly influenced purchasing patterns. This study investigates the impact of digital payment adoption on consumer spending, security concerns, and financial habits. A mixed-method research approach was used, incorporating primary data from 500 respondents (urban and rural India) and secondary data from RBI, NPCI, and industry reports. Findings indicate that digital payments increase consumer spending, promote financial inclusion, and facilitate seamless transactions, but concerns regarding security, fraud, and digital literacy persist. The paper also highlights 10 real-world case studies and provides recommendations to enhance trust and expand digital adoption.